Типи та автентичні зразки видів, описаних Д.М. Доброчаєвою - Ільїнська, А.П.; Протопопова, В.В.; Шевера, М.В. (Український ботанічний журнал, 2012)
На основании исследования научного вклада профессора Д.Н. Доброчаевой в систематику
растений обобщены данные о типах видов, описанных ученой (21): Сentaurea alutacea Dobrocz.,
C. czerkessica Dobrocz. et Kotov, C. nigriceps Dobrocz., C. pseudomaculosa Dobrocz., C. pseudo
coriacea Dobrocz., C. ternopoliensis Dobrocz., Anthemis subtinctoria Dobrocz., А. parviceps Dobrocz.
et Fed. ex Klokov, A. zephyrovii Dobrocz., Echium popovii Dobrocz., Myosotis popovii Dobrocz.,
Onosma guberlinensis Dobrocz. et Vinogr., O. macrochaetum Klokov et Dobrocz., O. volgense Dobrocz.,
Symphytum popovii Dobrocz., Spiraea litwinowii Dobrocz., Trapa danubialis Dobrocz., T. flero
vii Dobrocz., T. macrorhiza Dobrocz., Helianthemum creticola Klokov et Dobrocz., H. cretophilum
Klokov et Dobrocz. Некоторые типы и автентичние экземпляры выделены впервые. Для
каждого вида указаны категория типа, текст этикетки, место хранения типовых экземпляров и их номера. Кроме того, приведены сведения об автентичных и репрезентативных экземплярах, сделаны критические замечания. Research on scientific heritage of Professor D.M. Dobrochayeva in plant systematics resulted in
generalized data on typеs of the following species described by the scientist (21): Сentaurea alutacea
Dobrocz., C. czerkessica Dobrocz. et Kotov, C. nigriceps Dobrocz., C. pseudomaculosa Dobrocz.,
C. pseudocoriacea Dobrocz., C. ternopoliensis Dobrocz., Anthemis subtinctoria Dobrocz., А. parviceps
Dobrocz. et Fed. ex Klokov, A. zephyrovii Dobrocz., Echium popovii Dobrocz., Myosotis popovii
Dobrocz., Onosma guberlinensis Dobrocz. et Vinogr., O. macrochaetum Klokov et Dobrocz., O. volgense
Dobrocz., Symphytum popovii Dobrocz., Spiraea litwinowii Dobrocz., Trapa danubialis
Dobrocz., T. flerovii Dobrocz., T. macrorhiza Dobrocz., Helianthemum creticola Klokov et Dobrocz.,
H. cretophilum Klokov et Dobrocz. Some type and authentic specimens are determined for the first
time. For each of the species a category of type specimen, text of original herbarium label, location
in the Herbarium, and number are provided. Data on authentic and representative specimens and
critical comments are presented.